Free-Riding Behavior: Investment and Cooperation Strategies for Platform Supply Chain Blockchain Technology Considering Network Externality - Gui, Yunmiao; Gao, Xinyu; Feng Dong (International Journal of Industrial Engineering: Theory, Applications and Practice, 2026)
This paper investigates investment and cooperation strategies concerning blockchain technology within a platform supply chain comprising two suppliers under network externality. We develop a game-theoretic model of a platform supply chain that includes two directly competing suppliers and a platform. The study concludes that when only one supplier adopts blockchain technology, that is a scenario of partial cooperation, the other supplier may engage in free-riding by increasing its product price. The extent of this free-riding depends on the intensity of product competition, consumer trust in blockchain technology, and the strength of network externality. In the case of tripartite cooperation, where both suppliers adopt the technology, they may engage in bidirectional free-riding, which enhances their respective pricing power and profits. These findings suggest that the platform supply chain managers can leverage suppliers’ free-riding behavior to refine their blockchain investment and cooperation strategies.